Imaging Similarities Between Oral-Facial-Digital Syndrome Type 1 and Aicardi Syndrome: Prenatal and Postnatal Magnetic Resonance Imaging (MRI) Findings in 4 Patients. (February 2023) - Venkatesan, Charu; Countee, Elizabeth; Wong, Beatrix; Spaeth, Christine; Kline-Fath, Beth M.; Nagaraj, Usha D.
Prenatal identification by magnetic resonance imaging (MRI) of callosal anomalies, particularly with accompanying intracranial abnormalities, poses a challenge for accurate prognostication and fetal counseling as outcome can vary widely depending on underlying etiology. In female patients, Aicardi syndrome is an important consideration, and prompt postnatal ophthalmologic assessment to identify ocular stigmata of Aicardi syndrome can aid with anticipatory guidance and greater vigilance for seizures. We present a case of a female with fetal and postnatal MRI findings of agenesis of corpus callosum and type 2b interhemispheric cysts, characteristically found in Aicardi syndrome, but was found to have oral-facial-digital syndrome type 1 (OFD1). We also present 3 other companion cases with pre- and postnatal imaging of patients with Aicardi syndrome. These cases highlight the importance of widening the differential diagnosis to also include OFD1 for female patients with callosal anomalies.